PRODUKSI CABE KERING DAN ABON CABE OLEH TIM PKK DESA PADDINGING - Rahmawati; A. Muflihunna; St. Maryam (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2026)
Paddinging Village is one of the raw chili-producing areas in Takalar Regency. Every harvest season, the production of chili peppers is abundant. The limited consumption capacity of the community for chili peppers results in unsold harvests, exacerbated by the very short shelf life of fresh chili peppers, making them easily perishable. To anticipate this, the teaching team conducted community service aimed at preserving chili peppers into dried chili peppers, which are then processed into chili floss. This product is considered to have a long shelf life and can help residents maintain the availability of chili even outside the harvest season at an affordable price. Additionally, shredded chili products are chosen because they are delicious, easy to carry, long-lasting, and always needed as a side dish, especially for spicy food lovers. This activity was carried out using lecture, discussion, training, and PKM evaluation methods. The results obtained were that partners gained knowledge and skills on how to preserve chilies and produce chili floss.